Mid-infrared laser technologies for multiple compound gas sensing - Tao, Yuan (Nanyang Technological University, 2024)
NH3 and C2H4 are harmful gases that pollute the environment and pose risks to human health. Analyzing the photochemical cycles and sources of these two gases in the atmosphere requires accurate measurement of their concentrations. Gas detectors based on Quantum Cascade Laser (QCL) technology are currently the mainstream, offering advantages such as high sensitivity, wide spectral coverage, rapid response, reliability, stability, and non-contact detection. Additionally, the External Cavity Diode Laser Technique assumes a pivotal role in gas detection, particularly within the domains of spectral analysis and gas concentration measurement. Therefore, this study combines Quantum Cascade Laser (QCL) technology with External Cavity diode Laser Technique to design an External-Cavity Tunable Quantum Cascade Laser employed for the quantification of ammonia and ethylene gas concentrations. The experiment utilizes mid-infrared quantum cascade spectroscopy technology for simultaneous analysis and provides essential parameters for real-time monitoring of NH3 and C2H4 concentrations and chemical reaction analysis. This fusion of Quantum Cascade Laser technology and External Cavity diode Laser Technique in the gas detector not only enables efficient and accurate measurement of ammonia and ethylene concentrations but also provides reliable data support for environmental protection and human health.